2003
DOI: 10.1038/sj.leu.2402897
|View full text |Cite
|
Sign up to set email alerts
|

The presence of an HLA-identical sibling donor has no impact on outcome of patients with high-risk MDS or secondary AML (sAML) treated with intensive chemotherapy followed by transplantation: results of a prospective study of the EORTC, EBMT, SAKK and GIMEMA Leukemia Groups (EORTC study 06921)

Abstract: This report used the framework of a large European study to investigate the outcome of patients with and without an HLAidentical sibling donor on an intention-to-treat basis. After a common remission-induction and consolidation course, patients with an HLA-identical sibling donor were scheduled for allogeneic transplantation and patients lacking a donor for autologous transplantation. In all, 159 patients alive at 8 weeks from the start of treatment were included in the present analysis. In total, 52 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…[20][21][22] In a previous study by our group, we analyzed 100 patients in first complete remission who were candidates for SCT. 9,23 The 4-year disease-free survival rates in the donor versus no-donor groups were similar: 31% and 27%, respectively. This outcome suggests that patients with advanced stages of MDS may benefit both from allogeneic and from autologous SCT.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…[20][21][22] In a previous study by our group, we analyzed 100 patients in first complete remission who were candidates for SCT. 9,23 The 4-year disease-free survival rates in the donor versus no-donor groups were similar: 31% and 27%, respectively. This outcome suggests that patients with advanced stages of MDS may benefit both from allogeneic and from autologous SCT.…”
Section: Discussionmentioning
confidence: 77%
“…6 In the present study the non-relapse mortality was only 14% in the donor-group compared to 27% in the previous study. 9,23 Subgroup analysis of this study showed that the advantage of the presence of a donor was only apparent in the group of patients with intermediate and high risk cytogenetics (table 3). This observation is in line with the previous study 9 which showed only long-term survivors after autologous SCT in patients with good-risk characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of a large European study show that autologous HSCT can be recommended in patients with good-risk cytogenetic characteristics. 23 …”
Section: Mdsmentioning
confidence: 99%